TATA CARA DAN UPACARA SEPUTAR DAUR HIDUP MASYARAKAT JAWA DALAM SERAT TATACARA - Ekowati, Venny Indria (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2008)
This article is about a research study conducted to describe the life-cyclemanners and rituals according to a classical Javanese text titled Serat Tatacara (orST, for short) written by Ki and Nyai Padmasusastra in 1863-1904. The text, whichwas the subject under study, was in prose and published by Kangjeng Gupremen instBatawi in 1907 in 2 volumes, the 1 of which containing 22 chapters covering 80ndpages and the 2 containing 18 chapters covering 105 pages. The content ispresented in the form of dialogues or question-and-answer sessions betweenfamily members.The research data were compiled by careful and direct reading on thesubject. The instruments used for data compilation were data sheets. The data wereanalyzed by using a descriptive analysis technique practiced in such research.The result of the research is a description of the life-cycle manners andrituals implied in ST, which, on the basis of the research result, are grouped into 3phases: (1) the part covering the prenatal phase contains information aboutrecognizing signs of pregnancy, what are forbidden and what are recommendedduring pregnancy, the ritual feast held when the pregnancy is 1 and 9 months old,and the manners practiced during childbirth, (2) the part covering the postnatalphase contains information about how to sever the placenta and what to do with it,how to take care of the mother and the baby after childbirth, and the postnatalrituals from brokohan, held right after childbirth, to slametan nyapih, held at thetime the infant ceases being breastfed, and (3) the part covering childhood andadolescence contains information about the rituals of tetesan (the femalecounterpart of circumcision), pasah (the leveling of the horizontal edge of teeth),sukeran (banishment of bad luck), sunatan (circumcision), and tingalan (letting agirl be seen by visiting prospective parents-in-law) and the manners practiced byparents to find a spouse for their son or daughter.Keywords: manners and rituals, life cycle, Serat Tatacara